PENGARUH UPAH MINIMUM KABUPATEN/KOTA (UMK) TERHADAP TINGKAT PENGANGGURAN TERBUKA (TPT) DAN KEMISKINAN - Wildan Syafitri; Silvia Luthfiyah Ghinastri (Journal of Development Economic and Social Studies, 2024)
The Municipal Minimum Wage Policy (UMK) aims to improve the welfare of workers/laborers and avoid the poverty trap. However, based on the theory of the “UMK” policy, it has a negative impact, it can increase unemployment and poverty. This study analyzes the influence of the UMK on TPT and poverty in West Java by considering the supporting variables, namely population, number of industries, investment. The type of data used is secondary which tested by using panel data regression analysis and processed with Stata 14.2. The results of the analysis show that the UMK has a positive effect on TPT, but the population, number of industries and investment have no effect on TPT. Then, the UMK has a negative effect on poverty, population has a positive effect on poverty, and the number of industries has a negative effect on poverty, while investment has no effect on poverty in West Java in 2017 – 2021.